If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = 3 + 2j Solving 5 = 3 + 2j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-2j' to each side of the equation. 5 + -2j = 3 + 2j + -2j Combine like terms: 2j + -2j = 0 5 + -2j = 3 + 0 5 + -2j = 3 Add '-5' to each side of the equation. 5 + -5 + -2j = 3 + -5 Combine like terms: 5 + -5 = 0 0 + -2j = 3 + -5 -2j = 3 + -5 Combine like terms: 3 + -5 = -2 -2j = -2 Divide each side by '-2'. j = 1 Simplifying j = 1
| 14x-3=9x+5+63 | | 4n^2-22n=0 | | 243^3x=1/3 | | -20x6/5 | | -x+16=-0.5x+10 | | 4(v+1)+6=18 | | 20=4(c+1) | | (-2.75)x(-1.16)= | | 9x-49=x+7 | | 12d=-8 | | Y^2-6y+9=4y-12 | | 4/5=5/4v | | 4(7x+4)+31+(-46x)= | | 1/8m=5/2 | | B=48 | | 1/2-6/5=5/3 | | 12x+6-2x+9= | | x+(x+1)+(x+2)+(x+3)=74 | | 0.4(x+1)=5x+11.9 | | (3w-1)*w=96 | | 3-6x+2=-4x | | 3+18=0 | | (6x-8)-(8x+7)= | | 2x(3x-9)+2= | | 1v/321v=2 | | 7x+3y=3x+5y | | -3(s+2)=0 | | -2(r+-1)=0 | | 41=19-2a | | b+30+2b= | | 5/8k=21/2 | | 50=16p+2 |